Surgical mask and N95 in healthcare workers of Covid-19 departments: clinical and social aspects - Gelardi, Matteo; Fiore, Valeria; Giancaspro, Rossana; La Gatta, Emanuel; Fortunato, Francesca; Resta, Onofrio; Carpagnano, Giovanna Elisiana; Santomasi, Carla; Dimitri, Michela; Foschino Barbaro, Maria Pia; Lacedonia, Donato; Scioscia, Giulia; et al. (Acta Biomedica Atenei Parmensis, 2020)
Introdution. In order to prevent or slow down the transmission of COVID-19, various public health measures have been introduced, including social distancing, environmental disinfection and the use of personal protective equipment (PPE). In this perspective, the clinical practice of healthcare professionals has changed dramatically. As a matter of fact, the use of surgical masks and N95 has significantly worsened the job performance of workers who deal directly with COVID-19 disease. Methods. The study included 116 health workers employed in the pulmonology, intensive care and infectious diseases departments of Bari and Foggia Hospital, directly involved in the healthcare of patients affected by COVID-19. Between May 1, 2020 and May 31, 2020, each participant completed an online questionnaire aimed to investigate the impact of the COVID-19 pandemic on workers’ lifestyle changes and job performances. We compared the results based on the type of mask used by each participant (surgical mask vs N95). Results. Although disturbances related to the use of the mask arose earlier in subjects who wore the N95 (p = 0.0094), healthcare workers that wore surgical masks reported a statistically higher average score for a greater number of disorders. Conclusions. This is the first study that compares the effects of the two most used PPE on the quality of life of health workers and which highlights the greater discomfort caused by surgical masks. This result brings to light a serious social problem, being surgical masks widely used in everyday life by ordinary people and non-healthcare workers.